2015
DOI: 10.1093/nar/gkv020
|View full text |Cite
|
Sign up to set email alerts
|

RPI-Pred: predicting ncRNA-protein interaction using sequence and structural information

Abstract: RNA-protein complexes are essential in mediating important fundamental cellular processes, such as transport and localization. In particular, ncRNA-protein interactions play an important role in post-transcriptional gene regulation like mRNA localization, mRNA stabilization, poly-adenylation, splicing and translation. The experimental methods to solve RNA-protein interaction prediction problem remain expensive and time-consuming. Here, we present the RPI-Pred (RNA-protein interaction predictor), a new support-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
180
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(183 citation statements)
references
References 67 publications
0
180
0
Order By: Relevance
“…In addition to miRNAs, much evidence has demonstrated that lncRNAs, defined as a type of RNA with a length of > 200 nucleotides, can regulate physiological and pathological processes by interacting with DNA, RNA and protein molecules [8, 28, 29]. The lncRNAs are generally deregulated in a wide variety of diseases, including Alzheimer’s disease, heart disease and cancer [30-34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to miRNAs, much evidence has demonstrated that lncRNAs, defined as a type of RNA with a length of > 200 nucleotides, can regulate physiological and pathological processes by interacting with DNA, RNA and protein molecules [8, 28, 29]. The lncRNAs are generally deregulated in a wide variety of diseases, including Alzheimer’s disease, heart disease and cancer [30-34].…”
Section: Introductionmentioning
confidence: 99%
“…Several computational methods have been developed for predicting RNAprotein interactions [47,48,49,50,51]. In these methods, machine learning approaches, such as Fisher's linear discriminant analysis (LDA), support vector machine (SVM), and random forest (RF), were used to discriminate the interacting RNA-protein pairs from non-interacting pairs.…”
Section: Prediction Methods For Lncrna-protein Interactionsmentioning
confidence: 99%
“…These two methods focus on the prediction of lncRNA-protein interactions, and were benchmarked by using a few experimentally validated lncRNA-protein interactions, including HO-TAIR and XIST lncRNA. The third method, RPI-Pred [50], is a tool for predicting RNA-protein interactions using not only primary sequences but also the three dimensional structures of an RNA and a protein for the input data. In this method, structural motifs of proteins (called Protein Blocks)…”
Section: Prediction Methods For Lncrna-protein Interactionsmentioning
confidence: 99%
“…However, the three-dimensional configuration of MlrC-like protein or its interaction with MCYST-LR has not been worked out, although it could lead to valuable information related to the molecular structure, role and efficient binding with the protein. Theoretical approaches have been applied for structure prediction (Suresh et al, 2015). We report 3D structure of MlrC-like protein implementing a combined in silico approach like threading and abinitio for identification via composite modeling.…”
Section: Introductionmentioning
confidence: 99%